The Impact of Digital Transformation on Banking Financial Performance: an analytical study in the banking sector (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This study aims to investigate the impact of digital transformation on banking financial performance. Five banks (Al-Rigion Trade, Al-Mansour, Al-Nask Islamic, Jihane, and Asia Islamic Bank of Iraq) were selected as research sites. A final sample of 119 respondents was collected from 125. The descriptive-analytical approach was employed, using a questionnaire as the primary data collection tool. Statistical analysis utilized weighted mean, standard deviation, Pearson correlation coefficient, and simple linear regression. The five-point Likert scale measured respondents' perceptions. Key recommendations include investing in digital transformation, enhancing technological infrastructure, and improving financial processes.